Behavioural Ecology of Black-winged stilt (Himantopus himantopus Linn.) in Abhera wetland of Kota district, Rajasthan (International Journal of Scientific Research in Science and Technology, 2025)
Forests, meadows, wetlands, and deserts are just a few of the diverse environments where birds can be found. The connection between habitat and bird variety has been the subject of numerous studies. Ducks, geese, and swans are among the waterbirds that depend on wetlands as their home. Waterbirds can find food, refuge, and breeding places in wetlands. Understanding the life history and reproductive tactics of different bird species requires a thorough understanding of avian breeding biology. Because of its distinctive behaviors and adaptations throughout the breeding process, the Black-winged Stilt (Himantopus himantopus) stands out among these species as an interesting subject. A thorough grasp of the reproductive behaviors of the Blackwinged Stilt and the variables affecting nest site selection, courtship, incubation, hatching, parental care, and fledgling care can be obtained by incorporating results from several studies into each area of the breeding ecology. According to this study, environmental conditions can affect the nest architecture, with stilts modifying their patterns to maximize temperature regulation and shield eggs from predators.